Handgrip strength assessment at baseline in addition to bone parameters could potentially predict the risk of curve progression in adolescent idiopathic scoliosis - Lau, Rufina Wing Lum; Cheuk, Ka Yee; Hung, Vivian Wing Yin; Yu, Fiona Wai Ping; Tam, Elisa Man Shan; Wong, Lyn Lee Ning; Zhang, Jiajun; Lee, Wayne Yuk Wai; Cheng, Jack Chun Yiu; Lam, Tsz Ping; Lau, Adam Yiu Chung (Frontiers in Pediatrics, 2023)
Introduction Adolescent idiopathic scoliosis (AIS) is characterized by deranged bone and muscle qualities, which are important prognostic factors for curve progression. This retrospective case–control study aims to investigate whether the baseline muscle parameters, in addition to the bone parameters, could predict curve progression in AIS. Methods The study included a cohort of 126 female patients diagnosed with AIS who were between the ages of 12 and 14 years old at their initial clinical visit. These patients were longitudinally followed up every 6 months (average 4.08 years) until they reached skeletal maturity. The records of these patients were thoroughly reviewed as part of the study. The participants were categorized into two sub-groups: the progressive AIS group (increase in Cobb angle of ≥6°) and the stable AIS group (increase in Cobb angle <6°). Clinical and radiological assessments were conducted on each group. Results Cobb angle increase of ≥6° was observed in 44 AIS patients (34.9%) prior to skeletal maturity. A progressive AIS was associated with decreased skeletal maturity and weight, lower trunk lean mass (5.7%, p = 0.027) and arm lean mass (8.9%, p < 0.050), weaker dominant handgrip strength (8.8%, p = 0.027), deranged cortical compartment [lower volumetric bone mineral density (vBMD) by 6.5%, p = 0.002], and lower bone mechanical properties [stiffness and estimated failure load lowered by 13.2% (p = 0.005) and 12.5% (p = 0.004)]. The best cut-off threshold of maximum dominant handgrip strength is 19.75 kg for distinguishing progressive AIS from stable AIS (75% sensitivity and 52.4% specificity, p = 0.011). Discussion Patients with progressive AIS had poorer muscle and bone parameters than patients with stable AIS. The implementation of a cut-off threshold in the baseline dominant handgrip strength could potentially be used as an additional predictor, in addition to bone parameters, for identifying individuals with AIS who are at higher risk of experiencing curve progression.